Perception of the Impacts of Nature Tourism Development and Planning in Dong Hua Sao Protected Area, Laos - Wayakone , Sengdeuane (1996)
The study is concerned with an assessment of the opportunities for outdoor recreation development in the Dong Hua Sao protected area, located at the southern part of Laos (Champasak province). The study involves the assessment of the natural resources, the perception of residents towards socio-cultural, economic and physical impacts, and visitors' opinion towards activities and facilities preferred. The study reveals that the perception of the residents in Dong Hua Sao protected area is quite similar to results of other studies. The residents of DHS protected area believe that tourism will bring several changes to the social, economic and physical environments of the area. They feel that most of the changes will be beneficial for their community. Moreover, the residents have given higher priorities to issues related to employment and participation in culture practices for tourism, since these will lead to employment benefits. They also feel that deviant social activities should be viewed as one of the important criteria in judging the tourism's impacts. The result implies that the residents are sensitive to the future impacts caused by tourism and are able to judge the nature of impacts in relation to their needs and wants. The analysis of the visitors' opinions reveals that visitors are attracted to the protected area or park for its sight-seeing, bird and wildlife watching and nature education resources. Visitors are concerned with the level of development and have suggested that development be confined to nature tourism with traditional houses and nature resort that blends well with the natural environment. It can be implied from the analysis of the visitors opinion that tourism be developed without causing damages to the natural and cultural resources of the area. A recreation development plan is proposed based on the assessment of the resources and analysis of residents' attitude around the DHS protected area and visitors' opinion within the recreation areas in Champasak. Three areas are selected and 12 potential recreation sites within. It is recommended that the concept of development of the DHS recreation forests is the Forest Water Aesthetics and Adventure Touring. For each of the three areas, the development concept has also been formulated.